The use of social media and perception of body image and sense of coherence - Kłonowska, Martyna; Radlińska, Iwona (Journal of Education, Health and Sport, 2023)
Introduction and objective: One of the important factors that affect body perception is the beauty and body standards promoted by media and culture. Social media use can affect users’ self-perception and sense of coherence. The study aimed to assess whether and how social media impact for body perception and sense of coherence. Materials and methods: The study was conducted using an online questionnaire with a sample of 190 individuals, differentiated by gender. The Sense of Coherence Scale (SOC-29), Body Esteem Scale for Adolescents and Adults (BESAA), and a questionnaire developed for the study were utilized. Results: In the study group, as the daily time spent on social media increased, the sense of manageability (rho = -0.171, p = 0.018) and meaningfulness (rho = -0.166, p = 0.022), as well as the overall coherence score (rho = -0.155, p = 0.033), decreased. Longer usage of social media platforms was associated with lower scores on the appearance scale (rho= -0.260; p<0.001) and weight scale (rho= -0.240; p=0.001), while remaining independent of the scores on the attribution scale (p>0.05). Conclusions: The study shows that excessive use of social media can lead to a deterioration in body image and the amount of time spent on social media can contribute to the level of coherence. Conclusions highlight the need for implementing measures for the safe use of social media platforms and introducing psychoeducation on self-worth, body acceptance, and a sense of coherence, especially among young individuals.